Development of fludarabine formulations in the treatment of chronic lymphocytic leukemia - Ann Janssens; Marc Boogaerts; Gregor Verhoef (Drug Design, Development and Therapy, 2009)
Ann Janssens, Marc Boogaerts, Gregor VerhoefDepartment of Hematology, University Hospitals Leuven, Campus Gasthuisberg, Leuven, BelgiumAbstract: Fludarabine is an antineoplastic agent used in the treatment of hematological malignancies, particularly chronic lymphocytic leukemia (CLL) and indolent B-cell lymphoma. Because of its immunosuppressive effects, fludarabine has been added to reduced intensity conditioning regimens. The oral formulation of fludarabine has become widely available. Pharmacokinetic studies have shown that an oral dose of 40 mg/m2/d would provide systemic drug exposure similar to the standard intravenous (IV) dose of 25 mg/m2/d. The oral dose can be taken once daily without any dietary restrictions. Dose adjustments are mandatory in patients with renal impairment to avoid increased toxicity. Several noncomparative trials in previously untreated and treated patients with CLL have shown that treatment with the oral formulation demonstrates similar efficacy compared to historical control groups treated with the IV formulation. The tolerability profile of oral fludarabine seems similar to that of the IV formulation. Myelosuppression and infectious complications are the most frequently reported adverse events. Gastrointestinal toxicity is more frequent with the oral formulation, but is usually of mild or moderate severity. Although oral fludarabine makes treatment more convenient, health care workers must be aware of the compliance behavior of each patient. Keywords: CLL, treatment, oral fludarabine, intravenous fludarabine